2017
DOI: 10.1080/01658107.2017.1279640
|View full text |Cite
|
Sign up to set email alerts
|

Health Inequalities Associated with Post-Stroke Visual Impairment in the United Kingdom and Ireland: A Systematic Review

Abstract: The aim of this study was to report on the health inequalities facing stroke survivors with visual impairments as described in the current literature. A systemic review of the literature was conducted to investigate the potential health inequalities facing stroke survivors with subsequent visual impairments. A quality-of-evidence and risk-of-bias assessment was conducted for each of the included articles using the appropriate tool dependent on the type of article. Only four articles discussed health inequaliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…The National Clinical Guidelines for Stroke recommend orthoptists as a core stroke team member and all stroke survivors should be offered vision screening ( Intercollegiate Stroke Working Party 2016 ). This does not happen in some stroke units, representing a health inequality for stroke survivors ( Hanna and Rowe 2017 ). There is a high risk that stroke survivors without obvious signs of visual impairment never have their visual impairment detected and thus live with undiagnosed visual impairment and the consequences of this.…”
Section: Discussionmentioning
confidence: 99%
“…The National Clinical Guidelines for Stroke recommend orthoptists as a core stroke team member and all stroke survivors should be offered vision screening ( Intercollegiate Stroke Working Party 2016 ). This does not happen in some stroke units, representing a health inequality for stroke survivors ( Hanna and Rowe 2017 ). There is a high risk that stroke survivors without obvious signs of visual impairment never have their visual impairment detected and thus live with undiagnosed visual impairment and the consequences of this.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, inequalities may exist within the visually impaired stroke population on an individual level, in relation to demographic differences. A recent systematic review reporting health inequalities within the visually impaired stroke population concluded a lack of specific evidence within this area (Hanna & Rowe, 2017). However, unequal access to vision services after stroke based on area of residence was identified and called for national improvement (Rowe, 2013), although qualitative exploration is required to explore the views from this group specifically, in terms of health inequalities and psychosocial impact.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Furthermore, stroke and visually impaired groups individually presented with health inequalities (Hanna & Rowe, 2017), such as increased prevalence of stroke, poor recovery of impairments, and poor access to health services in subgroups such as older age, female gender, and lower socioeconomic status (Cumberland, Rahi, & UK Biobank Eye and Vision Consortium, 2016; Knight & Lindfield, 2015; Redfern, McKevitt, Rudd, & Wolfe, 2002). Therefore, it is possible that the combined group are facing issues that have not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…In Norway and internationally, there are lack of national care pathways for VIs after stroke in health care services [ 15 18 ], which has led to a variation in the quality of assessment and follow-up of VIs in stroke care [ 19 ]. In stroke services, there is a gap between research evidence on how to assess and follow up on VIs after stroke and clinical practice [ 11 , 20 ].…”
Section: Introductionmentioning
confidence: 99%